Supervise operation of the power plant using HMI system via GSM channel for control / Raden Eryanie Raden A. Othman - Raden A. Othman, Raden Eryanie (2014)
This paper present about the visualization system interface where technology and human are integrate. The systems helps to allow the contractor to easily monitor and compare the value to operating parameters such as historical data and alarm of the machines in the control room without having their presence at plant.